Comorbidities And Reducing InEquitieS (CARES): Feasibility of self-monitoring and community health worker support in management of comorbidities among Black breast and prostate cancer patients - Laura C. Schubel; Ana Barac; Michelle Magee; Mihriye Mete; Malinda Peeples; Mansur Shomali; Kristen E. Miller; Lauren R. Bangerter; Allan Fong; Christopher Gallagher; Jeanne Mandelblatt; Hannah Arem (Contemporary Clinical Trials Communications)
Background: Black individuals with cancer have a higher prevalence of comorbidities and a worse cancer prognosis than other racial groups in the US. As part of a quality improvement project, we aimed to demonstrate feasibility of self-monitoring and community health worker (CHW) support among managing comorbidities for Black individuals with breast or prostate cancer. Methods: In a single arm, pre-post study, we enrolled patients with diabetes and/or hypertension who identified as Black and were diagnosed with 1) stage 0-IV breast cancer, or 2) prostate cancer and on long-term androgen-deprivation therapy. Participants received a home-monitoring device linked to a mobile app and worked with a CHW over six months to track their blood pressure (BP) and/or blood glucose (BG). PROMIS surveys assessed support and self-efficacy. Results: Between May 2021–December 2022, 61 patients with breast or prostate cancer comorbid with hypertension (79 %) or hypertension and diabetes (21 %) enrolled. Once weekly self-recording of BP and BG was achieved in 92 % of individuals (with hypertension) and 77 % of individuals (with diabetes and hypertension). Participants (n = 47) who reported ≥4 readings in Months 1 and 6 demonstrated improved BP control (mean reduction = 4.07 mmHg); too few BG readings were collected to assess change. We observed a slight decrease in PROMIS scores for informational (mean 3.2, sd 8.0) and instrumental support (mean 3.6, sd 8.3). Conclusions: A self-monitoring and CHW intervention is a feasible approach to monitor hypertension among Black cancer patients. Modifications are needed to improve BG monitoring and patient reported outcomes.